Karma Sutras : leadership and wisdom for uncertain times - Chatterjee, Debashis (Haryana : Penguin Random House, 2021)
"Blurb Karma Yoga or Deep Work can simply be expressed by this formula: where p = actual performance P = potential i = interference Leaders get caught in co-relations and do not look at causalities. Minimizing interference (company cultures, 'I'/'Me' = Ego) to one's potential makes all the difference. Leadership is not about doing more, it is about observing more. Karma Sutras presents timeless leadership insights for the 21st century new managers. It vividly encapsulates the scientific and spiritual truths about organization, work, self-mastery and the purpose of leadership in the 4.0 VUCA world. Laced with small narratives from current issues to motivating stories and relatable quotes, the book caters to aspiring leaders and first-time managers alike. It provides deep anchors in spirituality for managers struggling in the post-COVID world. Debashis Chatterjee is Director at IIM Kozhikode, India and a globally published author"--